2021
DOI: 10.3390/app112110158
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Valorization of Solid Wastes from the Alcoholic Beverage Production Industry: Distilled Gin Spent Botanicals and Brewers’ Spent Grains

Abstract: In this paper, the authors assess the possibilities of energetic valorization for two solid wastes from alcoholic beverage production. Distilled gin spent botanicals (DGSB) and brewers’ spent grains (BSG) are tested, both by themselves and as co-substrates, for their possibilities as substrates for anaerobic digestion in a system of box-type digesters, suited for the process. While BSGs show a good performance for anaerobic digestion, DGSBs, despite showing an acceptable biomethanogenic potential result as not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moldgy and Parameshwaran investigated the properties of organic materials for waste heat recovery applications and found a high heat capacity [8]. Montes and Rico evaluated the possibility of applying energetic valorization to solid wastes from alcoholic beverage production and found that the use of waste material as a power source was possible given its high heating value [9]. Onorevoli et al presented a material with a high absorption potential which was acquired through energetic extraction from tobacco seeds, which is a material with high added value [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moldgy and Parameshwaran investigated the properties of organic materials for waste heat recovery applications and found a high heat capacity [8]. Montes and Rico evaluated the possibility of applying energetic valorization to solid wastes from alcoholic beverage production and found that the use of waste material as a power source was possible given its high heating value [9]. Onorevoli et al presented a material with a high absorption potential which was acquired through energetic extraction from tobacco seeds, which is a material with high added value [10].…”
Section: Introductionmentioning
confidence: 99%